1999
DOI: 10.1068/p281013
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Coding of Visual Patterns for the Blind

Abstract: Recognition tasks of simple visual patterns have been used to assess an early visual--auditory sensory-substitution system, consisting of the coupling of a rough model of the human retina with an inverse model of the cochlea, by means of a pixel-frequency relationship. The potential advantage of the device, compared with previous ones, is to give the blind the ability to both localise and recognise visual patterns. Four evaluation sessions assessed the performance of twenty-four blindfolded sighted subjects us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Furthermore, in order to enhance the similarity with the human visual system, the receptor field of the PSVA has a higher resolution in the center of the picture. Studies that have been conducted with auditory devices have shown the possibility of object localization (Auvray et al, 2007a;Renier et al, 2005a) and form recognition (Arno et al, 1999;Arno et al, 2001 with the PSVA; Cronly- Dillon et al, 1999Dillon et al, , 2000Pollok, Schnitzler, Mierdorf, Stoerig, & Schnitzler, 2005 with the Voice). Interestingly, recent studies have also demonstrated the possibility of recreating visual illusions with the PSVA (Renier et al, 2005b).…”
Section: Visual-to-auditory Substitution Devicesmentioning
confidence: 99%
“…Furthermore, in order to enhance the similarity with the human visual system, the receptor field of the PSVA has a higher resolution in the center of the picture. Studies that have been conducted with auditory devices have shown the possibility of object localization (Auvray et al, 2007a;Renier et al, 2005a) and form recognition (Arno et al, 1999;Arno et al, 2001 with the PSVA; Cronly- Dillon et al, 1999Dillon et al, , 2000Pollok, Schnitzler, Mierdorf, Stoerig, & Schnitzler, 2005 with the Voice). Interestingly, recent studies have also demonstrated the possibility of recreating visual illusions with the PSVA (Renier et al, 2005b).…”
Section: Visual-to-auditory Substitution Devicesmentioning
confidence: 99%
“…A quarter of the stimuli were the same as those used in the VHI experiment. The evaluation procedure was identical to the one used by Arno et al (1999). After each stimulus exploration, subjects re-created their observations with a set of metal bars.…”
Section: Experimental Designmentioning
confidence: 99%
“…Before performing the experiments, sighted and early blind subjects were trained to use the PSVA in a patternrecognition task. This training phase (adapted from Arno, Capelle, Wanet-Defalque, Catalan-Ahumada, & Veraart, 1999) consisted of five 1-h sessions preceded and followed by an evaluation session. The sighted subjects worked blindfolded.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The PVSA (Prosthesis Substituting Vision for Audition) uses pitch to encode position in both the horizontal and vertical axes. The PVSA also implements a bias inspired by the foveal region of the human eye, which dedicates more "space" to pixels in the centre of the field of view (Arno, Capelle, Wanet-Defalque, Catalan-Ahumada, & Veraart, 1999). An alternative approach is to sonify only those pixels that represent edges rather than surfaces.…”
Section: Sensory Substitutionmentioning
confidence: 99%